The potential of wild vegetation species of Eleusine indica L., and Sonchus arvensis L. for phytoremediation of Cd-contaminated soil - Amir Hamzah; Ricky Indri Hapsari; Rossyda Priyadarshini (Brawijaya University, 2017)
Phytoremediation has been intensively studied due its costs effectiveness and environmentally sound. Studies of heavy metal pollution phytoremediation has been done in develop countries, but still limited in Indonesia. This study aims to explore the potential of wild plant species Eleusine indica L. and Sonchus arvensis L. as an agent of phytoremediation on Cd-contaminated soil. This study was done descriptively in Pujon, Malang, Indonesia, to test the ability of two species of wild plants E. indica and S. arvensis in absorbing Cd. Along this research, plant growth and the concentration of Cd in roots, stems and leaves, was monitored. Plant growth was measured every week for three months. The plant roots, stems, and leaves collected separately, then analyzed its Cd levels. The results showed that both of two species of wild plants grew well on soil contaminated Cd. Plant roots can accumulate higher Cd than the stem part. In addition, E indica has the ability to accumulate Cd higher than S. arvensis, i.e. 57.11% and 35.84%, respectively